Genome assembly and transcriptome analysis provide insights into the antischistosome mechanism of Microtus fortis. (20th December 2020) - Li, Hong; Wang, Zhen; Chai, Shumei; Bai, Xiong; Ding, Guohui; Li, Yuanyuan; Li, Junyi; Xiao, Qingyu; Miao, Benpeng; Lin, Weili; Feng, Jie; Huang, Mingyue; et al.
Abstract: Microtus fortis is the only mammalian host that exhibits intrinsic resistance against Schistosoma japonicum infection. However, the underlying molecular mechanisms of this resistance are not yet known. Here, we perform the first de novo genome assembly of M. fortis, comprehensive gene annotation analysis, and evolution analysis. Furthermore, we compare the recovery rate of schistosomes, pathological changes, and liver transcriptomes between M. fortis and mice at different time points after infection. We observe that the time and type of immune response in M. fortis are different from those in mice. M. fortis activates immune and inflammatory responses on the 10th day post infection, such as leukocyte extravasation, antibody activation, Fc-gamma receptor-mediated phagocytosis, and the interferon signaling cascade, which play important roles in preventing the development of schistosomes. In contrast, an intense immune response occurrs in mice at the late stages of infection and could not eliminate schistosomes. Infected mice suffer severe pathological injury and continuous decreases in cell cycle, lipid metabolism, and other functions. Our findings offer new insights into the intrinsic resistance mechanism of M. fortis against schistosome infection. The genome sequence also provides the basis for future studies of other important traits in M. fortis .